Effect of Crohn's Disease on Villous Length and CYP3A4 Expression in the Pediatric Small Intestine. Issue 2 (16th December 2020) - Vyhlidal, Carrie A; Chapron, Brian D.; Ahmed, Atif; Singh, Vivekanand; Casini, Rebecca; Shakhnovich, Valentina
Abstract : Changes in absorptive capacity and first‐pass metabolism in the small intestine affect oral drug bioavailability. Characterization of such changes as a consequence of inflammation is important for developing physiologically‐based pharmacokinetic (PBPK) models for inflammatory bowel disease. We sought to elucidate the impact of small intestinal Crohn's disease (CD) on villous length and CYP3A4 expression in children. Freshly frozen duodenal and terminal ileum (TI) biopsies from 107 children (1–19 years) with and without CD were evaluated for active inflammation. Villous length and CYP3A4 mRNA/protein expression were compared among regions of active and inactive inflammation in CD and controls. A twofold reduction in villous length was observed in inflamed duodena and ilia of children with CD, but in the absence of regional inflammation, villi in CD were comparable in length to controls. Expression of CYP3A4 mRNA correlated significantly with villous length in the TI ( P  = 0.0003), with a trend observed in the duodenum that did not reach statistical significance. In the presence of active inflammation, a significant decrease in CYP3A protein expression was confirmed in the duodenum, where protein expression also correlated significantly with villous length across diagnoses ( P  < 0.0001). Our findings suggest that previous observations of decreased CYP3A4 expression and function in inflamed intestine may not be due solely to downregulation by inflammatory cytokines, but also to villous blunting and subsequent loss of surface area for protein expression. This information is relevant for PBPK model development and could aid with dose adjustment decisions for oral CYP3A4 substrates administered during CD flare (e.g., budesonide).